Penanganan Banjir di Kota Semarang Guna Menjamin Perlindungan dan Pengelolaan Lingkungan Hidup Berdasarkan Teori Walfare State - Pinasti, Shabrina Alifah; Ummi, Aulia Yudatining; Azzahro, Afifah Khoirunisa; Kamal, Ubaidillah (Media Hukum Indonesia (MHI), 2024)
The current state of global climate change has a significant impact on the environment, such as influencing variations in weather and climate patterns. This very significant climate change can cause natural disasters. For example, changes in rain patterns that increase the intensity of rain cause flooding. Semarang City is one of the big cities in Indonesia that experiences flooding every year. Floods mostly occur in downstream river basins, although flooding can also occur in several upstream river basins. The decreasing quality of the environment means that the survival of humans and other living creatures is in danger. It is very important that all stakeholders are involved in serious and consistent environmental protection and management. Stakeholders or the government are obliged to protect and manage the environment because it is in accordance with the Wellfare State principle, where this principle is the idea that the state is responsible for its citizens, namely by improving the welfare of its people through service, assistance, protection and prevention of social problems. The method used in this research is Normative Juridical. The result of this research is to find out how the Semarang city government handles floods in order to protect the community and manage the environment well.